Exploring the gut microbiota-Parkinson’s disease link: preliminary insights from metagenomics and Mendelian randomization - Liu, Jiaji; Wang, Le; Su, Ling; Chen, Jiayi; Su, Ruijun (Frontiers in Microbiology, 2025)
IntroductionThe relationship between the gut microbiome and Parkinson’s disease (PD) has recently attracted significant attention, with most studies focused on analyzing microbial composition. However, our understanding of the potential causal relationship between the gut microbiota and PD remains limited.MethodsWe extracted microbiome data from the metagenome for broad taxonomic coverage and accurate functional analysis. Subsequently, Mendelian randomization was employed to elucidate the causal relationship between the gut microbiome and PD.ResultsThe gut microbiota in PD patients was found to be systemically imbalanced, characterized by an abnormal enrichment of potential pathogenic bacteria, a significant reduction in key beneficial bacteria, and a reorganization of intestinal metabolic functions. This state of imbalance involves significant abnormalities in multiple metabolic and regulatory pathways, including the glucose metabolism, oxidative stress response, protein homeostasis regulation, and immune signaling pathways. These findings suggest that dysbiosis may influence host neural function through multilevel metabolic interventions. Additionally, specific microbial communities are clearly associated with disease risk, with some bacterial populations promoting disease onset and others demonstrating a potentially protective effect. Although metagenomic findings require validation in larger cohorts, the results of this study indicate that changes in gut microbiota composition and function are closely related to PD onset and progression.ConclusionThis study revealed that certain microorganisms traditionally considered beneficial may contribute to PD risk. This finding challenges previous assumptions and highlights the complexity of host–microbiome interactions. The identification of altered metabolic and immune pathways, particularly those involving bacteria that produce short-chain fatty acids, underscores the critical role of the gut microbiota in PD pathophysiology. However, the relatively small sample size of the current metagenomic analysis limits the generalizability of these findings. Larger, more diverse cohorts are needed to validate these results. Despite this limitation, the study provides important insights into microbiome-targeted therapeutic strategies, emphasizing the need to reconsider the roles of both beneficial and harmful microorganisms in PD.